Schradera involucrata is the correct name for Spermacoce scandens (Rubiaceae) - Delprete, Piero G.; Kirkbride, Jr., Joseph H. (Journal of the Botanical Research Institute of Texas, 2017)
In a recent article, the new combination Schradera scandens (Aubl.) Delprete was proposed. This binomial is predated by S. scandens Willd., which makes Delprete’s new combination a later homonym and thus illegitimate. Therefore, S. involucrata (Sw.) K. Schum. is accepted as the correct name to be used for this species.